VTuber concept review: The new frontier of virtual entertainment - Ferreira, Júlio César Valente; Regis, Rafael Dirques David; Gonçalves, Paula; Diniz, Gabriela Rodrigues; Tavares, Vitor Pedro da Silva Castelo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
Since the 2020s a phenomenon has been observed on live video platforms contemporarily to the COVID-19 pandemic, known as Virtual YouTubers, or VTubers. This type of content creator is based on the use of virtual avatars through motion capture and with intense use of digital art for the creation of online content, absorbing many characteristics of the Japanese subcultures otaku, kawaii, moe, among others, Japan being the country of origin of this type of content. Based on these aspects, we will conduct a narrative review and an overview of the state of the art regarding the concepts associated with VTubers and their quantitative data, focusing on the expansion of this type of content creator and how this cultural product establishes itself with a high degree of ascension rate within the scope of augmented reality/virtual reality, as well dialoguing with their transmedia strategies.